2019
DOI: 10.1002/jcc.26055
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Free Energy Calculations: The Combination between the Implicitly Polarized Fixed‐charge Model and the Reference Potential Strategy

Abstract: The IPolQ‐Mod charges, which are the average of two charge sets fitted in vacuum state and condensed phase, take account of polarization effect implicitly in the solvation free energy calculation. However, the performance of the IPolQ‐Mod charges sensitively depends on the QM levels used to generate the electrostatic potential from which the charges are fitted. In addition, the forces on atoms are not accurate theoretically in the molecular dynamics (MD) simulation as the solvent only feels the electrostatic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…This approach has also been used recently for free energy calculations by Jia and Li 35 and by Jia 35 and a modified form was used by Riquelme et al 34 Jia and Li found slightly improved results over those of the classical RESP partial charges on a small test set of molecules when using IPolQ-Mod. When correcting the endpoints using QM/MM, Jia and Li 35 and Jia 42 found the results improved and were similar to AM1-BCC. Riquelme et al's IPolQ-Mod results when using Minimal Basis Iterative Stockholder (MBIS) 49 charges rather than RESP charges achieved lackluster results in comparison with the simple and general AMBER force field (GAFF) 50 default charge method AM1-BCC, 51 and with their proposed method that used MBIS charges with post-simulation implicit polarization corrections.…”
Section: Single Simulationmentioning
confidence: 76%
See 1 more Smart Citation
“…This approach has also been used recently for free energy calculations by Jia and Li 35 and by Jia 35 and a modified form was used by Riquelme et al 34 Jia and Li found slightly improved results over those of the classical RESP partial charges on a small test set of molecules when using IPolQ-Mod. When correcting the endpoints using QM/MM, Jia and Li 35 and Jia 42 found the results improved and were similar to AM1-BCC. Riquelme et al's IPolQ-Mod results when using Minimal Basis Iterative Stockholder (MBIS) 49 charges rather than RESP charges achieved lackluster results in comparison with the simple and general AMBER force field (GAFF) 50 default charge method AM1-BCC, 51 and with their proposed method that used MBIS charges with post-simulation implicit polarization corrections.…”
Section: Single Simulationmentioning
confidence: 76%
“…41 The method has recently been applied to hydration free energy simulations of organic molecules and, in conjunction with the IPolQ-Mod partial charge method, yielded results similar to standard RESP and AM1-BCC free energies with GAFF on small test sets. 35,42 IPolQ is a recently developed method that calculates the electron density distribution of the solute based on measurements taken during explicit water simulation, 43 and then employs it to calculate polarized restrained electrostatic potential (RESP). 44 These charges are then averaged with charges derived for the solute in vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…Methods to correct fixed-charge simulation free energy calculations have been under investigation for several years. [36][37][38][39][40][41] Here we compare results with one such method which also used MBIS partial charges. In the method of Riquelme et al the cost of self-polarization was calculated post-simulation and added onto the ∆G hyd calculated using standard alchemical free energy change with molecular dynamics.…”
Section: Comparison With Post-simulation Self-polarization Calculationsmentioning
confidence: 99%
“…Another approach has been to account for polarization by way of a correction to the fixed-charge FF calculation. [36][37][38][39][40][41] Whereas polarization is indirectly included in the partial charges calculated for GAFF FFs, due to its choice of ab initio theory it is not specific to any particular solvent environment. Recent work of Zhou et al 42 has shown, based on comparisons of predicted with accurate/experimental molecular dipole moments in vacuum, that HF/6-31G* exhibits inconsistencies (ranging from under-to over-polarization by as much as 35 %).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation